Mississippi prisons as sites of environmental injustice: extreme heat, social death, and the state - Luzbetak, Austin, author; Opsal, Tara, advisor; Mao, KuoRay, committee member; Malin, Stephanie, committee member; Jacobi, Tobi, committee member (Colorado State University. Libraries, 2024)
Expanding on existing literature which understands incarcerated people as victims of environmental injustice and states as complicit actors in the production or allowance of environmental harm, I explore how incarcerated people in Mississippi experience extreme heat and how the state of Mississippi manages heat in state carceral facilities. I answer these questions by drawing on data from letter correspondence with people in three state prisons in Mississippi, as well as conducting critical policy analysis on relevant Mississippi laws, policy documents, and Department of Corrections reports. My findings from correspondence show that extreme heat amplifies the experience of "social death" already endemic to incarceration. More specifically, extreme heat intensifies incarcerated peoples' experiences of social disconnection and isolation, humiliation, and loss of sense of self, all of which produce social death. Moreover, state law and Mississippi Department of Corrections policy do not adequately protect incarcerated people from extreme heat, which I characterize as a state-green crime of omission. Instead, my findings from critical policy analysis demonstrate how the state of Mississippi is centrally focused on turning people in prison into laborers to maintain the state's carceral arm and provide benefits to counties, municipalities, and state agencies. I argue that these data have profound implications not only for environmental justice researchers and green criminologists, but more broadly for all who are interested in the project of prison abolition.